A simple Newtonian toy box approach to flood flow modeling, simulation and analysis - Mansos, John Francis L.; Real, Victoria Cassandra R.; Ricio, Dustin Edric L. (2013)
Two of the most common natural calamities in the Philippines are heavy rainfall and typhoon which both result to flood. As these calamities continue to surge the country, numerous methods are created to prevent their possible damages.
Flood simulation and modeling techniques are further developed to study the history, emergence, and prevention of past and even future typhoon occurrences that would cause disaster. Project NOAH, nababaha.com, and other useful software currently maintained by the government only determine flood history and specific typhoon phenomenon, while not speculating real occurrences of flood flow created by rainfall. The establishment of a proper drainage system is another problem in the country for existing systems do not suffice in reducing flood related casualties.
In line with this, it is imperative to create an alternative flood model that is both simple and adaptive, yet at the same time predictive. It needs to be able to simulate flood flow, giving considerations to various factors and constraints in the environment. This model needs to be adaptive yet simple enough for immediate usage, but equipped with results geared for a more detailed analysis--a flood model that can be used to help in the disaster preparedness of today, and a flood model that can be used on a long term investment for tomorrow.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman
Keywords: Flood forecasting -- Software; Typhoon -- Computer simulation; Hydrologic models; Project NOAH; Nababaha.com.; ClimateX; Newtonian toy box approach